Ectopic or aberrant thyroid side of the neck - Delgado, Bolívar; Rossi, Juan; Fernández, Isabel (Cirugía del Uruguay, 1994)
A case of ectopic thyroid or lateral aberrant of the neck is presented. Considerations are made on the possible pathogenical explanations for this type of finding.